MoS2 Nanosheets Anchored on Melamine‐Sponges‐Derived Nitrogen‐Doped Carbon Microtubes as Anode for High‐Rate Sodium‐Ion Batteries. Issue 20 (27th May 2019) - Feng, Meng; Zhang, Huizhen; Zhang, Yuchan; Zhang, Mengjie; Feng, Hongbin
Abstract: Here we demonstrate the design and synthesis of a composite electrode material consisting of MoS2 nanosheets anchored on nitrogen‐doped (N‐doped) carbon microtubes (NCMT) for anode applications in sodium‐ion batteries (SIBs). The NCMT skeleton was derived from the common melamine sponges, which was used not only as a template but also as the source of nitrogen and carbon. This smart design can effectively shorten the diffusion length of Na + ions, increase electric conductivity of the electrode, and provide more active sites for electrochemical reactions. When evaluated as anode for sodium‐ion batteries, the MoS2 @NCMT composites exhibited a larger initial coulombic efficiency (67.9%), high rate capability (196 mA h g −1 at 10 A g −1 and 118 mA h g −1 at 30 A g −1 ) and better cycling stability (289 mA h g −1 after 100 cycles at 80 mA g −1 ). Abstract : MoS2 nanosheets anchored on Melamine Sponges‐Derived nitrogen‐doped carbon microtubes displayed high‐rate capability in sodium‐ion batteries. This smart design can effectively shorten the diffusion length of Na + ions, increase electric conductivity of the electrode, and provide more active sites for electrochemical reactions.